Antifertility Activity of Aqueous Leaf Extract of Andrographis paniculata in Male Albino Rats - Senthil kumar, B (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe present study was to evaluate the effect of antifertility in aqueous leaf extract of Andrographis paniculata has been studied in Albino Rat. The study was divided into three groups of six animals for each. The first group (I) received distilled water serve as control. The second and third groups (II and III) of animals were administered the aqueous leaf extract daily on 100mg/kg body wt., and 200mg/kg body wt., respectively for a period of 45days significant decreases in the weights of testis, epididymes and seminal vesicle were observed. A dose related reduction in the testicular sperm count, epididymal sperm count and motility and abnormal sperm count were observed. The results suggest that the aqueous extract of the leaves of Andrographis paniculata has spermicidal activity.